Two cases of anaphylactic shock by methylprednisolone in neuromyelitis optica. (October 2018) - Takahashi, Keita; Asano, Tetsuya; Higashiyama, Yuichi; Koyano, Shigeru; Doi, Hiroshi; Takeuchi, Hideyuki; Tanaka, Fumiaki
Steroid pulse therapy with methylprednisolone (mPSL) succinate ester is the most common treatment for neuromyelitis optica (NMO); no cases of anaphylaxis have been reported to date. Here, we report two cases of anaphylactic shock induced by mPSL pulse therapy in patients with NMO and concurrent systemic lupus erythematosus. Both patients had received several courses of mPSL pulse therapy without any problems previously. Repeated mPSL pulse therapy and comorbid humoral autoimmune disease might increase the risk of anaphylaxis. Corticosteroids without succinate esters should be considered as an alternative therapy to prevent anaphylaxis.